Extension agents’ attitudes and participation in disseminating climate-smart agricultural practices in North-Central, Nigeria - Ojo, Ibukun Elizabeth; Kolawole, Ayorinde Ebenezer; Adeyonu, Abigail Gbemisola; Owolabi, Ayotunde Olayinka; Akerele, Dare; Awe, Toluwalase Eniola; Chike, Ikechukwu; Ogunsuyi, Deborah Pelumi; Ogundele, Abisola Adeola (Frontiers in Nutrition, 2025)
Low uptake of Climate-Smart Agricultural Practices (CSAPs) continues to exacerbate food insecurity and vulnerability in regions already burdened by poverty. CSAPs refer to agricultural methods that enhance productivity, climate resilience, and environmental sustainability. The effectiveness of extension agents is critical in promoting these practices, and their inefficiency can significantly weaken community resilience against hunger and environmental shocks. This study investigates the attitudes and participation of agricultural extension agents in disseminating CSAPs among rice farmers in North Central Nigeria. A multistage sampling procedure was used to select 88 extension agents. Data were collected using a questionnaire and analyzed using means, percentages, PPMC, and ordered probit regression. Results show that more than half of the extension agents (52.3%) exhibited unfavorable attitudes towards CSAPs, while 58% moderately participated in their dissemination. Participation was particularly low for water-smart mechanism such as index-based weather insurance (x¯=0.00), water harvesting (x¯=0.92), drip irrigation (x¯=0.73), as well as crop-smart mechanism like integrated pest management (x¯=0.62). among rice farmers. Training significantly influenced their attitudes (p = 0.011), age (p = 0.043), marital status (p = 0.028), household size (p = 0.026), occupation (p = 0.036), years of experience (p = 0.004), number of trainings (p = 0.035), and attitude (p = 0.000) significantly determined their participation levels. The study recommends targeted training and capacity-building initiatives to strengthen extension agents’ attitudes and participation in disseminating CSAPs. Such efforts are essential for strengthening climate resilience, enhancing food security, and promoting dietary diversity through the adoption of sustainable farming systems.